Phylogenetic Revision of Savoryellaceae and Evidence for Its Ranking as a Subclass - Dayarathne, Monika C.; Maharachchikumbura, Sajeewa S. N.; Jones, E. B. Gareth; Dong, Wei; Devadatha, Bandarupalli; Yang, Jing; Ekanayaka, Anusha H.; De Silva, Wasana; Sarma, Vemuri V.; Al-Sadi, Abdullah M.; Khongphinitbunjong, Kitiphong; Hyde, Kevin D.; et al. (Frontiers in Microbiology, 2019)
Morphology, phylogeny, and molecular clock analyses were carried out on Savoryellaceae in order to understand the placements of taxa in this family. Ascotaiwania and Neoascotaiwania formed a well-supported separate clade in the phylogeny of concatenated partial SSU, LSU, TEF, and RPB2 gene data. These two genera share similar morphological features, especially in their asexual morphs, indicating that they are congeneric. Hence, we synonymize Neoascotaiwania under Ascotaiwania. Ascotaiwania hughesii (and its asexual morph, Helicoon farinosum) and Monotosporella setosa grouped in a clade sister to Pleurotheciales and are excluded from Ascotaiwania which becomes monophyletic. A novel genus Helicoascotaiwania is introduced to accommodate Ascotaiwania hughesii and its asexual morph, Helicoon farinosum. A novel species, Savoryella yunnanensis is introduced from a freshwater habitat in Yunnan Province, China. Comprehensive descriptions and illustrations are provided for selected taxa in this family. In addition, we provide evolutionary divergence estimates for Savoryellomycetidae taxa and major marine based taxa to support our phylogenetic and morphological investigations. The taxonomic placement of these marine-based taxa is briefly discussed. Our results indicate that the most basal group of marine-based taxa are represented within Lulworthiales, which diverged from ancestral Sordariomycetes around 149 Mya (91–209) and Savoryellomycetidae around 213 Mya (198–303).